GEDUNG KAVALLERIE-ARTILLERIE PURA MANGKUNAGARAN SURAKARTA - Andereas Pandu Setiawan (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
This article is result of the research entitled Building Kavallerie Artillerie Pura Mangkunagaran Surakarta: Changes in Form and Function, conducted to answer the problem that focuses on three main points, which is why Kavallerie-Artillerie buildings in the complex of Pura Mangkunagaran was built, how the basic structure of Kavalerie-Artillerie Pura Mangkunagaran building and how changes in form and function that occur in Kavallerie- Artillerie Mangkunagaran Pura building. The purpose of this study is to trace the appearance of the building in the Pura Mangkunagaran environment, describing the shape of Kavallerie-Artillerie building, and describing and explaining the changes in form and function of Kavallerie-Artillerie Pura Mangkunagaran building within 135 years (1874- 2010), and the factors influencing them. To achieve the goals, the research was conducted by analysing multikausal historical approach that involves the use of Arnold Friedmann’s theory and the Talcott Parson’s theory of societal change to explore and discover the changes that occur. The study was done by direct observation and data collection in the field along with in-depth interviews supported by the data documents to generate the depth of meaning for this study. Changes in form and function that occur in the buildings of Kavallerie-Artillerie are influenced by political and military factors that appear in each period of Mangkunagaran conducted jointly with the Dutch colonial administration. These changes are also influenced by Mangkunagaran policy given to communities around Pura Mangkunagaran that foster community building settlers in Kavallerie-Artillerie. The results of this study are useful for policy-makers and local government all parties in Surakarta and Indonesia concerned to the direction of urban development and preservation of ancient buildings. Keywords: Change , Function, Kavallerie-Artillerie Building, Mangkunagaran